2009
DOI: 10.1136/bjsm.2008.056440
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and total serum cholesterol in rotator cuff tears: do they matter?

Abstract: There appears to be no association between serum triglyceride concentration and total serum cholesterol concentration in rotator cuff tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 35 publications
1
73
0
1
Order By: Relevance
“…Group 2 (control group) included 169 patients (115 men and 54 women; mean age: 61 years, range 26-86) who underwent arthroscopic meniscectomy for a meniscal tear in the same period, and had no evidence of back pain [23,24]. These patients were frequency-matched by age (within 3 years) and gender with patients of Group 1 ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Group 2 (control group) included 169 patients (115 men and 54 women; mean age: 61 years, range 26-86) who underwent arthroscopic meniscectomy for a meniscal tear in the same period, and had no evidence of back pain [23,24]. These patients were frequency-matched by age (within 3 years) and gender with patients of Group 1 ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies were conducted in older populations with at least one analysis group >50 years of age (33)(34)(35)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The range of symptom duration varied substantially within and across studies.…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 99%
“…Only 8 of the 44 studies reported insignificant findings throughout (33,38,46,48,51,58,67,68). Descriptions are provided below for the categories of biomarkers examined in >5 studies.…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 99%
See 2 more Smart Citations